Efektivitas Penataan Servicescape dalam Meningkatkan Kepuasan Konsumen Wingz O Wingz di Kota Bandung - Choir Wachidyantari; Maya Setiawardani (Ebiz Prima Nusa, 2022)
This research aimed to find out the effectivity of the servicescapes in order to increase the customers’ satisfaction of Wingz O Wingz in Bandung which was tested by distributing the questionnaires to 125 respondens. This research used a descriptive method with a quantitive approach. The result of the test indicates that servicescape layout in Wingz O Wingz is in good category and most of the customer feel satisfied by their services, then the servicescape layout has 61,3% positive impact to increasing customers’ satisfaction. Wingz O Wingz must pay attention to the servicescape layout and provide similar services in every branch.